2016
DOI: 10.1177/1941874416665744
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute Kidney Injury in Neurocritical Care Patients Receiving Continuous Hypertonic Saline

Abstract: Background and Purpose: Continuous intravenous 3% hypertonic saline (HTS) infusions are commonly used for the management of cerebral edema following severe neurologic injuries. Despite widespread use, data regarding the incidence and predictors of nephrotoxicity are lacking. The purpose of this study was to describe the incidence and identify predictors of acute kidney injury (AKI) in neurocritical care patients administered continuous infusion HTS. Methods: This was an institutional review board-approved, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
1
16
0
2
Order By: Relevance
“…In this study, PIPC/TAZ was identified as a significant risk factor of AKI in multivariate analysis. Erdman and colleagues reported that PIPC/TAZ was an independent risk factor of AKI in neurocritical care patients receiving continuous infusion of hypertonic saline [15]. Our results also showed that PIPC/TAZ increases the risk of AKI.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, PIPC/TAZ was identified as a significant risk factor of AKI in multivariate analysis. Erdman and colleagues reported that PIPC/TAZ was an independent risk factor of AKI in neurocritical care patients receiving continuous infusion of hypertonic saline [15]. Our results also showed that PIPC/TAZ increases the risk of AKI.…”
Section: Discussionsupporting
confidence: 79%
“…However, of these studies, only five involved continuous administration of hypertonic saline and were thus included for data synthesis (Fig. 1, Table 1) [10][11][12][13][14]. The overall quality of the studies as determined by the Newcastle-Ottawa scale ranged from fair to good, and most were limited by follow-up length and comparability of the study groups (Table 2) [10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Erdman et al [14] conducted a two-center retrospective cohort review to assess predictors of acute kidney injury in 337 patients receiving hypertonic saline infusion for severe neurological injuries-113 with ischemic strokes. Acute kidney injury occurred in 16% of patients receiving hypertonic saline.…”
Section: Resultsmentioning
confidence: 99%
“…There is no definitive data whether one hyperosmolar agent is superior to the other, and the choice can be guided by their individual side effects. Potential complications of HTS use are fluid overload, pulmonary edema, hypokalemia, cardiac arrhythmias, hyperchloremic metabolic acidosis, acute kidney injury, and dilutional coagulopathy ( 63 , 64 ). To avoid rebound edema, HTS should be gradually tapered and the serum sodium level should never be allowed to drop more than 10–12 mEq/L over 24 hours ( 63 , 65 ).…”
Section: Icu Managementmentioning
confidence: 99%